Agricultural education-actuality and Ambition - Alzobaidy , Dakhel Hussein; Mohammed, Mohammad A. (Al-Mukhtar Journal of Sciences, 2003)
Education is considered to be one of the important stratigical steps for development, because of the changes in the individual behavior due to experience, work, and practice. The agricultural education means that process through which the individual educates some technical and agricultural practices. The goal of agr. Education is to affect on peoples to achieve the behavioral changes needed which consequently contribute in improving the productive efficiency. The changes in the system of education have to be formalized in accordance with development requirements. The research also included the agr. Education between the pest and now in Gamaheria, also the preparation for secondary and preparatory agr. Education in faculties of agriculture in Gamaheria.